Radioactivity concentration of 14C in the air of 14C urea breath test rooms and the resulting internal dose to medical staff - Bei Yu; Fei Chen; Jing Cao; Dingxin Long (Radiation Medicine and Protection)
Objective: To monitor the radioactivity concentration of 14C in the air of rooms used to perform 14C urea breath tests, and evaluate the contamination status of 14C released during such tests, and assess the occupational health risk to medical staff working in such areas. Methods: 14CO2 in air was absorbed from the air and turned into calcium carbonate through a chemical reaction. Then, calcium carbonate was prepared into a suspension in a low-potassium glass vial. The sample was analyzed using a low-background liquid scintillation counter. Results: The radioactivity concentrations of 14C in air of the breath-test rooms in hospitals and physical examination institutions range from 1.35 to 18.41 Bq/m3. The annual committed dose for medical staff was estimated to be between 2.01 × 10−2 and 2.74 × 10−1 μSv. Conclusions: Our results reveal a significant increase of 14C radioactivity concentration in the air of breath-test rooms, but the resulting committed dose is much lower than the limits prescribed by the International Commission on Radiological Protection (ICRP). However, the potential risk of long-term exposure to low-dose radiation should be paid more attention.